Massoud Mohammed's Human-Centric Analysis of History - Saeed Othman, Hardi Hama; Abdalla, Shabaz (Universitas Islam Negeri Raden Intan Lampung, 2025)
This research delves into Massoud Mohammed's philosophy and theory of human interpretation of history, his different analyzes and interpretations of history form an essential component of his comprehensive philosophical framework and fundamental criticism of Marxist ideology. The main objective is to examine Massoud Mohammed's analysis of the restoration of the role and position of man as an active engine of the movement of history and in turn to dismantle Marxist theory and interpretation of history. Addressing the main research questions: What are the ideologies that undermine the position and role of man in the movement of history? What are the principles of life management, human roles, aspirations, positions and duties in Massoud Mohammed's analysis? What are Massoud Mohammed's criticisms of Marxism and materialist historical interpretation? Our research carefully follows all stages of scientific research, using historical-analytical research methods,We have analyzed Massoud Mohammed's theory of interpretation of history, evaluated Massoud Mohammed's writings, works and theory of human interpretation of history., The main findings emphasize that Massoud Mohammed, as a Kurdish thinker, is the first to have his own views on the interpretation of history. As a result of his in-depth, detailed and comparative readings, he presents his theory by criticizing Marxism and materialist interpretation of history.